2010
DOI: 10.1002/cjoc.201090298
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Interesting Gas‐phase Rearrangement Reactions of 2‐Pyrimidinyloxy‐N‐arylbenzylurea Promoted by Urea‐Carbamimidic Acid Tautomerism by ESI‐MS/MS and Theoretical Computation

Abstract: The gas-phase rearrangement reactions of compound 1, 2-dimethoxypyrimidinyloxybenzylaminobenzenedipropylurea, were studied by ESI-MS/MS. The experimental results showed that introduction of dipropylurea moiety into the molecule initiated various interesting gas-phase chemistries and the mechanisms were proposed on the basis of hydrogen/deuterium (H/D) exchange experiments and theoretical computations. Moreover, product 2, the solution-phase rearrangement product of compound 1, was synthesized and its gas-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…It is becoming increasingly recognized that the gas‐phase Smiles rearrangement is not confined to the classical five‐membered ring transition state. For example, both Wang and Pan proposed transition states of six‐membered rings, supported by theoretical calculations 24–28 . In addition, Pan's group highlighted that carbon monoxide (CO) could be eliminated through a three‐membered ring transition state 29 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is becoming increasingly recognized that the gas‐phase Smiles rearrangement is not confined to the classical five‐membered ring transition state. For example, both Wang and Pan proposed transition states of six‐membered rings, supported by theoretical calculations 24–28 . In addition, Pan's group highlighted that carbon monoxide (CO) could be eliminated through a three‐membered ring transition state 29 .…”
Section: Introductionmentioning
confidence: 94%
“…For example, both Wang and Pan proposed transition states of sixmembered rings, supported by theoretical calculations. [24][25][26][27][28] In addition, Pan's group highlighted that carbon monoxide (CO) could be eliminated through a three-membered ring transition state. 29 Concerning the extrusion of sulfur dioxide (SO 2 ), Lu and Irikura suggested that this process occurred through a five-membered ring transition state.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, both Wang and Pan proposed transition states of six-membered rings, supported by theoretical calculations. [24][25][26][27][28] Additionally, Pan's group highlighted that carbon monoxide (CO) could be eliminated through a three-membered ring transition state. 29 Concerning the extrusion of sulfur dioxide (SO 2 ), Lu and Irikura suggested that this process occurred through a five-membered ring transition state.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Thus, the reactivity and structures of the reactive transient intermediates can then be further studied by MS/MS to provide clues for the study of reaction mechanisms. [27][28][29] The gas phase results of reaction system can reflect the system in liquid phase, [30,31] according to the gas phase results obtained by ESI-MS/MS, we can understand the process in the solution phase. Then we also synthesized the authentic Pd(IV) complex 3c•OAc and tried to ana-lyze it by ESI-MS/MS to further confirm the characteristic of the intercepted Pd(IV) transient intermediate in reaction solution.…”
Section: Introductionmentioning
confidence: 99%